Dynamics of Curriculum Development in Islamic Religious Education Learning at MA Syarif Hidayatulloh - Fitriyani Kosasih; Rikza Priawan; Asep Rahmat; Muhammad Abduh; M. Darmawan A.Aziz (Universitas Muhammadiyah Enrekang, 2022)
In the curriculum development process, of course, dynamics will be encountered, as happened at Syarif Hidayatulloh Islamic High School, West Bandung Regency, which has experienced several changes in curriculum development along with developments in the learning side of Islamic Religious Education. The purpose of this research is to find out how the dynamics of curriculum development in learning Islamic education at MA Syarif Hidayatulloh. This type of research is qualitative research using qualitative methods, namely observation, interviews or document review. The results of the research show that the curriculum is a collection of a set of values ​​designed to be transformed to students, both values ​​in cognitive, affective and psychomotor forms. By obtaining a set of these values, the mindset and behavior of students will be formed in accordance with the directions and objectives that have been formulated previously, namely the curriculum. Curriculum development goals must also pay attention to institutional goals, curricular goals, and instructional goals. On the other hand, it can be emphasized that the goals of curriculum development cannot be separated from the goals of education itself, because the curriculum is the ideal spearhead of the vision, mission and goals of a nation's education. However, dynamics will certainly be encountered in the curriculum development process, such as what happened at Syarif Hidayatulloh Islamic High School, West Bandung Regency, which has undergone several changes in curriculum development in line with developments in the learning aspect of Islamic Religious Education.